Conducting Criminological Fieldwork in China: a Guanxi Approach? - Yuan, Xiaoyu (Asian journal of criminology, 2018)
Conducting criminological fieldwork in a non-Western society remains a fascinating and mysterious enterprise. Among existing studies, very few have systematically examined the process and dynamics of conducting fieldwork in the Chinese criminal justice context. This study, based on the author’s own experiences, reflects on the key stages in such fieldwork, including obtaining access to research, interviewing and observing, and addressing ethical concerns. At its core, the study seeks to examine two key dynamics, guanxi and mianzi, focusing on how they work and the ways in which they can shape the outcomes of fieldwork. This study serves as a preliminary step in the hope that future research that endeavors to develop indigenous criminology in China will provide a proper theoretical framework and a more systematic examination.